Name‐Based Autoconfiguration for Mobile Ad hoc Networks - Kim, Namhoon; Kang, Saehoon; Lee, Younghee; Lee, Ben (ETRI journal, 2006)
ABSTRACT In a mobile ad hoc network, difficulties exist in supporting address autoconfiguration and naming resolution due to the lack of centralized servers. This letter presents a novel approach, called name‐based autoconfiguration (NBA), which uses host names to determine IP addresses and provides address autoconfiguration and name resolution as a single protocol.